AURORA KINASES: STRUCTURE, FUNCTIONS AND THEIR ASSOCIATION WITH CANCER - Kollareddy, Madhu; Dzubak, Petr; Zheleva, Daniella; Hajduch, Marian (Biomedical papers, 2008)
Background: Aurora kinases are a recently discovered family of kinases (A, B & C) consisting of highly conserved serine\threonine protein kinases found to be involved in multiple mitotic events: regulation of spindle assembly checkpoint pathway, function of centrosomes and cytoskeleton, and cytokinesis. Aberrant expression of Aurora kinases may lead to cancer. For this reason the Aurora kinases are potential targets in the treatment of cancer. In this review we discuss the biology of these kinases: structure, function, regulation and association with cancer.Methods and Results: A literature search.Conclusion: Many of the multiple functions of mitosis are mediated by the Aurora kinases. Their aberrant expression can lead to the deregulation of cell division and cancer. For this reason, the Aurora kinases are currently one of the most interesting targets for cancer therapy. Some Aurora kinase inhibitors in the clinic have proven effectively on a wide range of tumor types. The clinical data are very encouraging and promising for development of novel class of structurally different Aurora kinase inhibitors. Hopefully the Aurora kinases will be potentially useful in drug targeted cancer treatment.
Keywords: Aurora kinases/Serine/threonine/Spindle/Centrosomes/Cytoskeleton/Cytokinesis/Oncogenes